Other Avenues What Balanchine can tell us about the Kirov - Simpson, Jane (Dance Books Ltd., Alton,Hampshire (UK), 2001)
The Kirov/Balanchine equation. There may be economic or technical reasons for the hard shoes, but the noise is a serious intrusion and it takes a conscious effort to filter it out and the Kirov needs to sort it out, soon. PALABRAS CLAVE: Serenade, Apollo, Symphony in C, Kirov Ballet, George Balanchine repertoire.